Enforcing strict guidelines and regulations for express bus companies in hiring competent bus drivers in Malaysia / Fatma Diyana Hassan … [et al.] - Hassan, Fatma Diyana; Mohd Noordin, Nabila; Azid, Nur Ashikin; Zaina, Zurazreen (2011)
Recently accident case involving express bus in Malaysia is increasing especially during festive season. Even the government took precautions for example Code of Practice in managing the scheme of work of express bus however, the increasing cases showed, the regulations and guidelines need to be more strict and the enforcement of the guidelines and regulations should be strictly commanded by authorized body. Although there is guidelines and regulations to be followed by the companies, however the guidelines for the express bus companies to hire competent express buses drivers is not included and the observation from the authority should be compulsory and strictly be enforced because we are dealing with many lives of the passengers of the express bus in which should be protected in this issue.